Allergy and asthma prevention 2014. Issue 6 (October 2014) - Nieto, Antonio; Wahn, Ulrich; Bufe, Albrecht; Eigenmann, Philippe; Halken, Susanne; Hedlin, Gunilla; Høst, Arne; Hourihane, Jonathan; Just, Jocelyne; Lack, Gideon; Lau, Susanne; Matricardi, Paolo Maria; et al.
Abstract Asthma and allergic diseases have become one of the epidemics of the 21st century in developed countries. Much of the success of other areas of medicine, such as infectious diseases, lies on preventive measures. Thus, much effort is also being placed lately in the prevention of asthma and allergy. This manuscript reviews the current evidence, divided into four areas of activity. Interventions modifying environmental exposure to allergens have provided inconsistent results, with multifaceted interventions being more effective in the prevention of asthma. Regarding nutrition, the use of hydrolyzed formulas in high‐risk infants reduces the incidence of atopic dermatitis, while there is for now not enough evidence to recommend other dietary modifications, pre‐biotics, probiotics, or other microbial products. Pharmacologic agents used until now for prevention have not proved useful, while there is hope that antiviral vaccines could be useful in the future. Allergen‐specific immunotherapy is effective for the treatment of allergic patients with symptoms; the study of its value for primary and secondary prevention of asthma and allergy is in its very preliminary phases. The lack of success in the prevention of these disorders lies on their complexity, which involves many genetic, epigenetic, and environmental interactions. There is a need to identify target populations, involved mechanisms and interactions, and the best interventions. These must be effective, feasible, implementable, and affordable.